Two-point observations of low-frequency waves at 67P/Churyumov-Gerasimenko during descent of PHILAE: Comparison of RPCMAG and ROMAP - Richter,I; Auster,H-U; Berghofer,G; Carr,CM; Cupido,E; Fornacon,K-H; Goetz,C; Heinisch,P; Koenders,C; Stoll,B; Tsurutani,BT; Vallat,C; et al. (Annales Geophysicae, 2016)
The European Space Agency’s spacecraft ROSETTA has reached its final destination,comet 67P/Churyumov-Gerasimenko. Whilst orbiting in the close vicinity of the nucleus theROSETTA magnetometers detected a new type of low-frequency waves possibly generated by across-field current instability due to freshly ionized cometary water group particles. During separation, descent and landing of the lander PHILAE on comet 67P/Churyumov-Gerasimenko, weused the unique opportunity to perform combined measurements with the magnetometers onboardROSETTA (RPCMAG) and its lander PHILAE (ROMAP). New details about the spatial distributionof wave properties along the connection line of the ROSETTA orbiter and the lander PHILAEare revealed. An estimation of the observed amplitude, phase and wavelength distribution will be presented as well as the measured dispersion relation, characterizing the new type of low-frequencywaves. The propagation direction and polarization features will be discussed using the results of aminimum variance analysis. Thoughts about the size of the wave source will complete our study